Jordskifteretten som arena for konfliktløsning - Kåre Sky (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2022)
Land consolidation courts deal with cases where the relationship between holders of grazing rights needs be regulated, but also where the rights holders are competing with other potential land uses, such as building holiday cabins, forestry, hunting, etc. In this essay we follow a couple that consider to apply for land consolidation due to conflicts.
Keywords: K11; Q15; 330; Land Consolidation; Rules of joint use; Dispute resolution; Grazing